POSITIVE, NEGATIVE, UNKNOWN: ASSUMPTIONS OF HIV STATUS AMONG HIV-POSITIVE MEN WHO HAVE SEX WITH MEN - Parsons, Jeffrey T. (2006)
Serosorting (i.e., engaging in unprotected sex with partners known to be of the same serostatus) can be a difficult process for men who have sex with men (MSM) who frequently make assumptions about their partners’ serostatus. This process can be further complicated by a partner’s dishonesty as well as other individual and contextual factors. The present study specifically examined how assumptions of serostatus made about unknown serostatus partners impact on the sexual behavior of 110 alcohol-abusing HIV-positive MSM. Although previous research has shown that HIV-positive MSM are more likely to serosort with other known HIV-positive men than with known HIV-negative men, our data suggest that unprotected sex behavior may not be specifically driven by whether or not they made assumptions of seroconcordance or serodiscordance. The types of assumptions these HIV-positive MSM made about their unknown status sexual partners and the basis for such assumptions were also examined. Owing to the ambiguities involved in assumptions of a partner’s serostatus in sexual encounters, the “unknown status” partner category is analytically distinct from “known status” categories, and needs to be more fully explored because of its impact on perceived serosorting, rather than actual serosorting, among HIV-positive men.